Photolabile protection for amino acids: studies on the release from novel benzoquinolone cages - Fonseca, Andrea Susana Cabral da (2015)
The synthesis of a novel fused nitrogen heterocycle, benzoquinolone, for evaluation as a photocleavable protecting group is described for the first time, by coupling to model amino acids (alanine, phenylalanine and glutamic acid). Conversion of the phenylalanine ester conjugate to the thionated derivative was accomplished by reaction with Lawesson’s reagent. Photocleavage studies of the carbonyl and thiocarbonyl benzoquinolone conjugates in various solvents and at different wavelengths (300, 350 and 419 nm) showed that the most interesting result was obtained at 419 nm for the thioconjugate, revealing that the presence of the thiocarbonyl group clearly improved the photolysis rates, giving practicable irradiations times for the release of the amino acids (less than 1 minute).